The myth of silent spring : rethinking the origins of American environmentalism - Montrie, Chad (University of California Press, 2018)
"The Myth of Silent Spring challenges the widely held belief that Rachel Carson's celebrated 1962 book catalyzed the American environmental movement. While acknowledging the important contribution of Carson's exposé, this book draws on a bounty of rich sources to push the movement's origins further back in time. It recognizes a long line of overlooked historical actors and identifies several other critical factors behind the rise of modern environmental thinking and protest. Recovering this slighted history helps us to better understand who should count as an 'environmentalist' and what should count as 'environmentalism,' essential insights for building a hardy environmental movement today and in the future"--Provided by publisher.